Impoverishment of Perpetrators of Criminal Acts of Corruption as A Form of Punishment Alternative - Sasmita , Rangga; Khatab , Muhammad; Machmud, Aris (Yapilin Press, 2026)
Corruption in Indonesia has become a complex issue, systematically, structurally, and massively damaging the governance system. As a result, the exercise of state power cannot fully focus on public interest due to the widespread influence of corrupt behavior. This situation has raised public concern over the increasing prevalence of corruption, which causes significant losses to the state. This article employs a juridical legal approach. The findings indicate that impoverishment can serve as an alternative punishment that effectively deters corrupt actors. However, efforts to eradicate corruption through the impoverishment of corruptors in Indonesia have not been optimally implemented. The legal process has not yet exerted significant pressure through the confiscation of assets obtained from corruption or the restitution of state losses resulting from such crimes. A firmer implementation is necessary so that corruptors face a real deterrent effect in accordance with applicable laws and regulations. This research is expected to assist in identifying and analyzing the current legal regulations related to the impoverishment of perpetrators of corruption crimes, particularly in the context of asset confiscation from criminal proceeds. In addition, this research aims to examine and evaluate the implementation of court decisions against perpetrators of corruption crimes concerning asset recovery or the confiscation of unlawfully acquired wealth.